Investigation of p16INK4a as a prognostic biomarker in oral epithelial dysplasia. (26th December 2013) - Nankivell, Paul; Williams, Hazel; Webster, Keith; Pearson, David; High, Alec; MacLennan, Kenneth; Senguven, Burcu; McConkey, Christopher; Rabbitts, Pamela; Mehanna, Hisham
<x xml:space="preserve">Abstract</x> Background Human papilloma virus is a risk factor for oropharyngeal cancer. Evidence for a similar aetiological role in the development of oral dysplasia or its transformation to oral cancer is not as clear. Meta‐analyses estimate the prevalence of high‐risk human papilloma virus (HPV) serotypes to be three times higher in pre‐malignant lesions and cancer than in normal oral mucosa. However, this does not imply a causal relationship. Conflicting results are reported from the few studies examining the prognostic significance of HPV positivity in the development of oral cancer. We aimed to examine the ability of p16INK4a protein expression, a surrogate marker of HPV infection, to predict malignant progression in a large cohort of oral dysplasia patients. Methods One hundred forty eight oral dysplasia cases underwent immunohistochemical analysis using a monoclonal antibody against p16INK4a. Clinical factors were also collated on each case. Slides were double scored independently by two trained observers. Univariate analyses using both logistic and Cox regression models were performed. Results Thirty nine of 148 cases progressed to cancer. Ten of 148 cases (7%) were p16INK4a positive. High grade of dysplasia (P = 0.0002) and lesion morphology (P = 0.03) were found to be prognostic of malignant progression. p16INK4a score was not prognostic in this cohort (P = 0.29). This did not change with a time to event analysis (P = 0.24). Conclusion Few studies have assessed the aetiological role of HPV in cancer development from dysplastic lesions. Our study, using one of the largest cohorts of oral dysplasia, demonstrated a low rate of p16INK4a positivity and was unable to confirm a prognostic ability for this biomarker.